CD47-Dependent Molecular Mechanisms of Blood Outgrowth Endothelial Cell Attachment on Cholesterol-Modified Polyurethane - Ueda, Masako (2010)
We previously showed that blood outgrowth endothelial cells (BOECs) had a high affinity for polyurethane (PU) covalently configured with cholesterol residues (PU-Chol). However, the molecular mechanisms responsible for this enhanced affinity were not determined. CD47, a multifunctional transmembrane glycoprotein involved in cellular attachment, can form a cholesterol-dependent complex with integrin α(v)β(3) and heterotrimeric G proteins. We tested herein the hypothesis that CD47, and the other components of the multi-molecular complex, enhance the attachment of BOECs to PU-Chol. Immunoprecipitation studies, of human and ovine BOECs, demonstrated that CD47 associates with integrin α(v) and integrin β(3) as well as G (αi-2) protein. The three-fold increase in BOEC attachment to PU-Chol, compared to unmodified PU, was reversed with the addition of blocking antibodies specific for CD47 and integrin α(v) and integrin β(3). Similar results were observed with the addition of methyl-beta-cyclodextrin (MβCD), a known disruptor of the CD47 complex as well as of the membrane cholesterol content, to seeded BOEC or PU-Chol films. Reducing CD47 expression, via lentivirus transduced shRNA, decreased BOEC binding to PU-Chol by 50% compared to control groups. These data are the first demonstration of a role for the CD47 cholesterol-dependent signaling complex in BOEC attachment onto synthetic surfaces.